Dampak Food Waste terhadap Biaya Operasional pada Usaha Kuliner Skala Kecil: Studi Kasus Donat Fitri Palu - Felicia Pavita Cendana; Revalino Juan Farel; Ernawaty Usman; Abdul Pattawe; Sugianto (Tangible Journal, 2026)
Food waste is often considered a significant operational cost burden for culinary businesses. This study analyzes the real impact of food waste on cost efficiency at Donat Fitri Palu, a small-scale culinary business. The researchers used a descriptive qualitative approach, collecting data through in-depth interviews, observation, and documentation of production activities. The main findings reveal an interesting fact: Donat Fitri Palu does not implement a formal cost accounting system, but instead uses “intuitive cost control” that relies heavily on market experience. This strategy is realized through dynamic adjustments to daily production volumes in order to proactively respond to consumer demand. This approach has proven successful in significantly reducing food waste, while unsold products that are still fit for consumption are not considered a total loss, but are managed as surplus food through discount pricing or distribution to employees. The results of this study prove that a targeted intuitive control strategy can minimize the impact of food waste losses and directly contribute to the cost efficiency of MSME operations.